Analysis of the Implementation of the Purchase Accounting Information System at PT Indonesia Asahan Aluminum - Aryati; Hazmi , Yusri; Agustina, Monika; Kanizia, Kisyfa; Ramadhan, Ryan Albi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Study This aim For evaluate application System Information PT Indonesia Asahan Aluminum Accounting with compare theories proposed by experts with implementation in the company. The analytical method used is descriptive For inspect grooves spatial and purchase invoices in a way systematic. Inalum apply procedure purchase from reporting inventory in warehouse until reception goods through system E. Procurement computerized. System purchase at Inalum covers function related, documents, notes accounting, procedures, elements internal control, and charts flow system accountancy purchase. Although Inalum has operate procedure in accordance standard operational, still found constraint in spread document related purchase. Repair in matter This expected can increase efficiency operational and optimize management document company